Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1161/01.cir.89.1.285
|View full text |Cite
|
Sign up to set email alerts
|

Fast computed tomography detection of coronary calcification in the diagnosis of coronary artery disease. Comparison with angiography in patients < 50 years old.

Abstract: Although the specificity to detect angiographically significant coronary disease with fast CT improves in a younger patient population, it continues to be relatively low. In contrast to older patient populations, a small but significant number of patients < 50 years old with angiographically significant coronary artery disease do not have coronary calcification demonstrated by fast CT. Thus, caution should be used in excluding significant coronary artery disease on the basis of a negative fast CT study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 18 publications
1
40
0
4
Order By: Relevance
“…31 A study by Fallavollita and associates, 32 however, suggested that this degree of accuracy in identifying coronary disease may not be possible in all patient groups. In their investigation of 106 patients younger than 50 years, the negative predictive value for significant angiographic disease overall was only 85%.…”
Section: Coronary Calcium and Luminal Disease Severitymentioning
confidence: 99%
“…31 A study by Fallavollita and associates, 32 however, suggested that this degree of accuracy in identifying coronary disease may not be possible in all patient groups. In their investigation of 106 patients younger than 50 years, the negative predictive value for significant angiographic disease overall was only 85%.…”
Section: Coronary Calcium and Luminal Disease Severitymentioning
confidence: 99%
“…The presence of CAC can be assessed noninvasively using either EBCT or MDCT. Although several studies have revealed a correlation between CAC and angiographic stenosis, [10][11][12][13][14][15][16] few studies have used MDCT and it is unknown whether the CAC score is the most important predictor of significant coronary stenosis as assessed by CAG independent of other factors, such as age, body mass index and medication. To evaluate the clinical significance of the CAC score determined by MDCT, we compared coronary artery stenosis as assessed by CAG with the CAC score, coronary risk factors and medications.…”
mentioning
confidence: 99%
“…Fallavollita JA et al compared the EBCT detection of calcium with coronary angiography in 106 patients and found an 85% sensitivity and 45% specificity in detecting significant stenos. 25,26 Four patients who had calcification detected at CT scan did not have angiographically detectable disease and were classified as false positive cases while determining test performances. It is highly probable that these individuals had atherosclerosis that was not detected on the angiography either because of compensatory enlargement of the arteries or because diffuse atherosclerosis causing narrowing of the entire lumen so that no focal stenosis was visible on angiography.…”
Section: Discussionmentioning
confidence: 99%